WANPRESTASI DALAM PELAKSANAAN PEMBELIAN DENGAN PEMBAYARAN SECARA ANGSURAN DENGAN PT MIZUHO LEASING INDONESIA - Rezky Fabyo Darussalam; Talitha Atha Shakira; Muhammad Kareem Maulana Nugroho (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Motor vehicle credit allows gradual purchase with installment payments over a specified period, although interest becomes an additional burden. Customers can choose credit service providers, such as leasing companies, offering financing options for capital goods with installment payments or operating leases. However, this periodic payment system often faces challenges when debtors default or fail to pay installments each month. This non-payment is considered a default, a violation of the motor vehicle purchase agreement. This research examines the factors causing defaults in the implementation of motor vehicle credit by PT. Mizuho Leasing Indonesia, particularly in the case involving Mr. Giki Argadiraksa. The discussion involves the concepts of performance and default in contract law, where performance is an obligation that must be fulfilled by the debtor according to the agreement. Default, on the other hand, occurs when the debtor fails to meet obligations as agreed. The factors causing defaults in the context of motor vehicle installment payments are analyzed through Supreme Court decisions. In handling default cases, legal efforts that can be pursued involve the judicial process. This research aims to further understand the dynamics of defaults in motor vehicle credit payments, provide legal insights, and investigate legal efforts that can be taken by both parties to resolve the default case.